2022
DOI: 10.1136/bmjgh-2021-007899
|View full text |Cite
|
Sign up to set email alerts
|

Introducing field digital data collection systems into seasonal malaria chemoprevention campaigns: opportunities for robust evidence development and national e-health strategies

Abstract: Seasonal malaria chemoprevention (SMC) is a World Health Organization-recommended intervention to protect children under the age of 5 in Africa’s Sahel region. While SMC remains highly effective in decreasing malaria cases, implementing countries face several challenges regarding collecting quality data; monitoring coverage and compliance and overcoming delays in campaigns due to late payment to field distributors.To address these challenges, the National Malaria Control Programmes of Benin, The Gambia, Ghana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For instance, in seasonal malaria chemoprevention campaigns in Africa's Sahel region, digital data collection reduced working time and costs compared to paper-based tools. 21 Similarly, a study from Zanzibar found that direct data entry via personal digital assistants was faster and cheaper than the paper-based system, while also avoiding common errors associated with the manual process. 22 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, in seasonal malaria chemoprevention campaigns in Africa's Sahel region, digital data collection reduced working time and costs compared to paper-based tools. 21 Similarly, a study from Zanzibar found that direct data entry via personal digital assistants was faster and cheaper than the paper-based system, while also avoiding common errors associated with the manual process. 22 …”
Section: Discussionmentioning
confidence: 99%
“…During the 2020 campaigns, three countries used digital data collection, The Gambia, Ghana and Benin. In 2021, a further three countries piloted digitalisation, Nigeria, Burkina Faso and Guinea [ 2 ], with other countries expressing interest of using these tools for future campaigns. Therefore, the lack of smartphones/tablets should not be seen as a long-term barrier to uptake, as video resources can increasingly be viewed on tools provided by the SMC campaign.…”
Section: Discussionmentioning
confidence: 99%
“…Community health worker (CHW) programmes rely on effective training and supervision [ 1 ]. The increasing use of mobile devices by community health programmes in Africa [ 2 ], and increasing personal ownership of smartphones [ 3 ], creates opportunities to use video to explain complex tasks during pre-service training and for community health workers to refer to as job-aids. However, although mobile phones have been used in primary health programmes [ 4 , 5 ], the use of video job-aids has not yet been widely exploited or evaluated in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings indicated that routine microscopy or RDT would miss a large portion of subclinical malaria infections. In addition, the use of intermittent preventative treatment in pregnancy (IPTp) in this very low prevalence of subclinical malaria setting in Myanmar is less advantageous compared to an Africa setting where prevalence of malaria infection is higher in pregnant women and ITPp is a proven method for prevention of malaria in pregnancy due [42][43][44]. However, the burden of subclinical malaria in Asia should not be neglected as adverse pregnancy outcomes associated with malaria infection are still a concern.…”
Section: Factors Associated With Subclinical Malaria Among Pregnant W...mentioning
confidence: 99%